Kocuria indica sp nov., isolated from a sediment sample - Dastager, Syed Gulam; Tang, Shan-Kun; Srinivasan, Krishnamurthi; Lee, Jae-Chan; Li, Wen-Jun (International Journal of Systematic and Evolutionary Microbiology, 2014)
An actinobacterial strain was isolated from a sediment sample from Chorao Island, in Goa province, India, and subjected to a taxonomic investigation. The isolate, designated NIO-1021(T), was a Gram-stain positive, aerobic, non-motile and coccoid. Strain NIO-1021(T) was identified as a member of the genus Kocuria by a polyphasic approach. Strain NIO-1021(T) could be differentiated from other members of the genus Kocuria on the basis of physiology and 16S rRNA gene sequence analysis. The 16S rRNA gene sequence similarity of strain NIO-1021(T) to the most closely related species, Kocuria marina KCTC 9943(T), was 98.6% with 19 nt differences). Furthermore, DNA-DNA hybridization analysis revealed that the novel strain had lower relatedness with the type strains of other members of the genus Kocuria. The strain formed a monophyletic clade with K. marina with 100% bootstrap values. The major phospholipids were phosphatidylglycerol, diphosphatidylglycerol and two unidentified lipids. The predominant menaquinone was MK-7(H-2). The major fatty acids were anteiso-C-15:0, iso-C-(16:0) and anteiso-C-17:0. The DNA G+C content of strain NIO-1021(T) was 60.5 mol%. Chemotaxonomic and phylogenetic properties of the strain were consistent with its classification as representing a member of the genus Kocuria. On the basis of phenotypic, chemotypic and molecular characteristics, strain NIO-1021(T) is considered to represent a novel species of the genus Kocuria, for which the name Kocuria indica sp. nov. is proposed, with strain NIO-1021(T) (=NCIM 5455(T)=DSM 25126(T)=CCTCC AA 209050(T)) as the type strain.